Complete Genome Sequencing and Transcriptome Analysis of Nitrogen Metabolism of Succinivibrio dextrinosolvens Strain Z6 Isolated From Dairy Cow Rumen - Hailemariam, Samson; Zhao, Shengguo; Wang, Jiaqi (Frontiers in Microbiology, 2020)
The unclassified Succinivibrionaceae lineages are abundant in high yielding multiparous cows and their presence is positively correlated with milk yield and fat composition; and reduces methane emissions. However, it is still unclear which species are associated with the most efficient feed nutrient utilization and productivity. Here, we used integrated whole genome sequencing, MALDI-TOF MS, coupled with phenotypic and chemotaxonomic analysis, to characterize S. dextrinosolvens Z6 a species in Succinivibrionaceae isolated from the rumen. To assess the role of S. dextrinosolvens Z6 in nitrogen metabolism, cells grown in different nitrogen sources were analyzed by RNA-sequencing. The whole genome sequence result revealed that genome size of 3.47 Mbp with 38.9% of G + C content. A total of 2,993 encoding sequences account 98%. The genes for regulating carbohydrate 10.6% and amino acid 9% transport and metabolism were the most abundant. ANI (Average nucleotide identity) showed SD-Z6 was most closely related to SD-22B (99.96%). The whole genome alignment of SD-Z6 with SD-22B showed that more than 0.34 Mb nucleotides difference. Growth of SD-Z6 occurred at a temperature 36 to 42oC with optimum 39.7oC, pH 6 to 8, the optimum pH was 6.9 and with 0 to 1% (w/v) NaCl. The maximum growth (OD600 0.825 ± 0.12) and MCP (178.2 µg/ml) was observed in cell gown in amino acid. The maximum concentration of ammonia (3.96 ± 1.2) was observed in urea containing media and 1.06 mM (26.7% of the produced) remains remained after 24hr incubation. Activities of urease and GS (P<0.01) and GDH (P<0.05) were significantly different in nitrogen and growth phase. GOGAT (P<0.01) was significantly different only at different growth phase. In total, 1246 differentially expressed genes were identiﬁed in all nitrogen. Among differentially expressed genes 33 were related to nitrogen metabolism. Their expression correlated with nitrogen sources and the intensity of enzyme activity. This result enhances our understanding of the roles Succinivibrionaceae in the efficient feeds nutrient utilization and on environmental protection.